Solvability for a Class of Logarithmic Type Initial Conditions of Hadamard Fractional Differential System on an Infinite Interval (Journal of Nonlinear Modeling and Analysis, 2026)
This paper investigates a class of Hadamard fractional differential system involving logarithmic type initial conditions on an infinite interval. Based on some obtained properties of the Green's functions, Schauder fixed point theorem and Banach contraction mapping principle, we establish the existence and uniqueness results for the system. Finally, we illustrate examples which show our main results.
Keywords: Solvability; Hadamard fractional differential system; logarithmic type initial conditions; infinite interval